Analysis of The Effect of Dividend Policies on Corporate Value With Good Corporate Governance (GCG) as Moderating Variables - Mirna Indah Nurlita; Tri Gunarsih (Universitas Teknologi Yogyakarta, 2021)
This research examines the moderating effect of Good Corporate Governance (GCG) in the relationship between dividend policy and publicly listed firms' corporate value in the Corporate Governance Perception Index (CGPI) index in 2011-2018. The independent variable is dividend policy, which is proxies using the Dividend Payout Ratio (DPR), Good Corporate Governance as a moderating variable, which is proxies by using the Good Corporate Governance (GCG) score, and company size (SIZE) as the control variable. Company value is determined by the price-book value (PBV). This research uses quantitatively based explanatory research. This study's purpose was to decide how the independent variable affects the dependent variable to determine the moderating variable's effect, whether it will enhance or weaken the independent variable's influence. The population included in this study was all publicly traded companies that participated in the 2011-2018 Corporate Governance Perception Index (CGPI). The sample of this analysis comprised nine firms, so that there were 72 test objects. Data analysis used multiple linear regression and moderated regression analysis (MRA). Based on the study that dividend policy impacts company value, Good Corporate Governance (GCG) cannot moderate the relationship between dividend policy variables on firm value, and firm size is not a control variable in this study.